Moodle-Based Virtual Class to Improve Students' Metacognition and Independence in Online Learning - Pratama, Muh. Putra; Sampelolo, Rigel; Karuru, Perdy (Journal of Education Technology, 2024)
Metacognition and learning independence are important aspects in education that affect students' ability to manage and control their learning process. This study aims to analyze the use of Moodle-based virtual learning platform in improving students' metacognition and learning independence. This research designs and develops vitual learning that can be accessed by all junior high school students openly and free of charge which is packaged with an interactive display using Moodle learning is more interesting, interactive and fun so that students' digital literacy and learning independence increase. The stages refer to the ADDIE development model. The research stages were conducted by following the ADDIE development model (Analysis, Design, Develop, Implement, and Evaluate). The data collection approach involved various techniques such as questionnaires, FGDs, observation, documentation, interviews, and tests. Based on the results of the practicality test of using moodle, it can be concluded that the user's response after using moodle and filling out the assessment questionnaire with the results of user answers is in the comfortable category. So, user responses strongly agree to use moodle in learning. The results of the feasibility and practicality test of moodle that has been developed can be a reference to be continued to a broader stage and in terms of development can be a reference to be developed again both in terms of content/material and appearance. So, the user response is strongly agree to the application of online learning as an interactive media in learning.